Prevalence and profiles of unmet healthcare need in Thailand - Thammatacharee, Noppakun (BioMed Central, 2012)
BACKGROUND: In the light of the universal healthcare coverage that was achieved in Thailand in 2002, policy makers have raised concerns about whether there is still unmet need within the population. Our objectives were to assess the annual prevalence, characteristics and reasons for unmet healthcare need in the Thai population in 2010 and to compare our findings with relevant international literature. METHODS: A standard set of OECD unmet need questionnaires was used in a nationally-representative household survey conducted in 2010 by the National Statistical Office. The prevalence of unmet need among respondents with various socio-economic characteristics was estimated to determine an inequity in the unmet need and the reasons behind it. RESULTS: The annual prevalence of unmet need for outpatient and inpatient services in 2010 was 1.4% and 0.4%, respectively. Despite this low prevalence, there are inequities with relatively higher proportion of the unmet need among Universal Coverage Scheme members, and the poor and rural populations. There was less unmet need due to cost than there was due to geographical barriers. The prevalence of unmet need due to cost and geographical barriers among the richest and poorest quintiles were comparable to those of selected OECD countries. The geographical extension of healthcare infrastructure and of the distribution of health workers is a major contributing factor to the low prevalence of unmet need. CONCLUSIONS: The low prevalence of unmet need for both outpatient and inpatient services is a result of the availability of well-functioning health services at the most peripheral level, and of the comprehensive benefit package offered free of charge by all health insurance schemes. This assessment prompts a need for regular monitoring of unmet need in nationally-representative household surveys.